2015
DOI: 10.1007/s12010-015-1754-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical Values of Porosity in Rice Cultures of Isaria fumosorosea by Adding Water Hyacinth: Effect on Conidial Yields and Quality

Abstract: Conidia of the entomopathogenic fungus Isaria fumosorosea are used to control insect pests in crops. Commercially available mycoinsecticides manufactured with this fungus are produced on a large scale via solid-state cultures (SSC). In order to favour gaseous exchange in SCC, texturizers can be added to increase porosity fraction (ε). This work presents results of water hyacinth (Eichhornia crassipes) as a novel texturizer. A mixture of parboiled rice (PR), with a ε = 0.23, was used as a substrate, which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
6
0
6
Order By: Relevance
“…On the other hand, the use of cheap texturizers mixed with the initial dry-substrate in cycle 1 could be an interesting alternative. The use of water hyacinth or sugar cane bagasse improve the porosity of rice, which in turn, increase oxygen and heat transfer across the substrate bed [17,8]. Therefore, it is probable that the use of these kinds of materials from the beginning of the rst cycle could allow the substrate to be reused for at least one more cycle without needing extra drying or sterilization steps.…”
Section: Fourth Production Cycle Using Recycled Ricementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of cheap texturizers mixed with the initial dry-substrate in cycle 1 could be an interesting alternative. The use of water hyacinth or sugar cane bagasse improve the porosity of rice, which in turn, increase oxygen and heat transfer across the substrate bed [17,8]. Therefore, it is probable that the use of these kinds of materials from the beginning of the rst cycle could allow the substrate to be reused for at least one more cycle without needing extra drying or sterilization steps.…”
Section: Fourth Production Cycle Using Recycled Ricementioning
confidence: 99%
“…Production of Metarhizium robertsii Xoch 8.1 conidia in successive production cycles AE 6Á7 × 10 7 a 1Á4 × 10 9 AE 3 × 10 8 b 1Á2 × 10 9 AE 1Á3 × 10 8 b 6Á0 × 10 8 AE 6Á2 × 10 7 a Productivity (con gds −1 d −1 ) 5 Á7 × 10 7 AE 6Á7 × 10 6 a 2Á4 × 10 8 AE 5 × 10 7 b 2Á1 × 10 8 AE 2Á1 × 10 7 b 1Á0 × 10 8 AE 1 × 10 7 a AESD) followed by the same letter within the same line are not significantly different according to the Tukey method (P < 0Á05) Cuapio et al 2015;da Cunha et al 2020)…”
mentioning
confidence: 92%
“…Rice has a high capacity to absorb water (2.8 mL g of rice −1 ), and the amount of free water to carry out the ionic conduction is low. On the other hand, corn stubble that was used to increase porosity and improve O 2 transfer through the support also contributed to resistivity, due to the air gaps formed by the rice and corn stubble (Angel-Cuapio et al, 2015). Therefore, based on these results and considering previous studies where it has been shown that at intensities above 20 V the metabolism of fungi can be inhibited (Velasco-Alvarez et al, 2011), a current density of 0.09 mA cm −2 (1.3 mA) was selected according to electrode surface (14.13 cm −2 ) to develop a cell potential of 10 V for this study.…”
Section: Characterization Of the Electrochemical Cellmentioning
confidence: 99%
“…Rodriguez-Gomez et al (2009) evaluated different substrates in surface culture for conidia production of Beauveria bassiana, finding the highest production on Sabouraud dextrose agar, and maintaining a high degree of virulence on Tenebrio molitor. Another strategy was the use of support material to increase the porosity of the packing bed in solid state cultivation of Isaria fumosoroseae that may increase oxygenation and conidiation even at 100% (Angel-Cuapio et al, 2015) without affecting virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Como se mencionó, el sustrato sólido más utilizado para la producción de conidios de HE ha sido el arroz, por su equilibrio nutricional, costo, tamaño, forma del grano y propiedades de hidratación e integridad estructural, incluso después de la colonización por hongos (López-Pérez et al, 2015). Se ha utilizado el arroz combinado con varios texturizantes para cambiar la porosidad del medio (Muñiz-Paredes, 2016;Ángel-Cuapio, 2011;Gómez-Preciado, 2014), con esto se evita que el sustrato se compacte, se incrementa el área de contacto entre sustrato y el microorganismo, además de facilitar la trasferencia de oxígeno y bióxido de carbono (Ángel-Cuapio et al, 2015).…”
Section: Discussionunclassified